Breeding of a new ornamental and edible plum cultivar Hongying - WANG Xuesong; LI Siyu; CHEN Lei; CUI Long; ZHANG Yanbo (Guoshu xuebao, 2025)
Hongying is a new ornamental and fresh-eating variety developed by Jilin Academy of Agricultural Sciences through artificial hybridization between Peacock Egg Seedling as the female parent and Purple Leaf Plum as the male parent. In 1992, the artificial hybridization was conducted. The hybrid seeds were sown in spring of 1993, and the results were obtained in 1998. The content of soluble solids was 14.2% in 2004. In 2006, it was used as a primary superior line for high-grafting observation, and the line code was 92-1-3. In 2012, regional tests were carried out in Jilin, Gongzhuling, Changchun, Panshi, Linjiang and Huinan. Production trials were carried out at Gongzhuling in 2016. The tree posture is semiopen, and the tree growth vigor is strong. The average length of one-year-old branches can reach to 117 cm. The leaf is lanceolate and convex, and the blade edge is obtusely serrated, 7.83 cm in length and 3.54 cm in width. The fruit is round, the fruit top is flat, and the suture is shallow. The peel is purple-red, and flesh is red and soft, with moderate juice content, fine fiber, sticky core, sweet and sour flavor, full mature aroma, and fresh food quality. The average single fruit weight is 19.7 g, the longitudinal diameter is 2.99 cm, and the transverse diameter is 3.01 cm. Soluble solids content is 16.9%, titratable acid content is 1.03%, soluble sugar content is 8.41%, flavonoids content is 33.71 mg·100 g-1, anthocyanins content is 58.33 mg·100 g-1, and carotenoids content is 96.44 mg·100 g-1. It blooms in late April in Gongzhuling, and the flowering period is 7-10 days. The fruit matures in late July, and the fruit growth period is 80 days. It has strong cold resistance, excellent resistance to plum red spot disease, and medium resistance to brown rot. The variety is of ornamental value and has strong branching ability. The 1-year-old branches, young leaves, young fruits and fruit stalks are red. The color of newly growing leaves in spring is relatively light, usually red or lavender, while in summer and autumn, the color of leaves turns to deep purple and the color of petals is white. The fruit skin color is purple red. It is suitable for introduction and trial planting in Jilin Province and similar areas with frost-free period ≥ 130 days and above 2800 ℃ effective accumulated temperature ≥ 10 ℃. Orchards should be chosen on flat terrain, deep soil, neutral acid sandy loam; grafting rootstocks should choose cherries or plums. The planting density is 3 m × 4 m. The grafting union should be slightly higher than the ground during planting, and irrigation should be immediately performed after planting. Topdressing should be applied before flowering, vigorous growth stage and veraison stage in the growing season. In the first two times, nitrogen fertilizer should be mainly applied, and in the veraison stage phosphorus and potassium fertilizer should mainly utilized. After harvest, the fruit should be treated with decomposed organic manure, 20-30 kg per plant. Immediate irrigation should be done after fertilization, and the amount of water should be controlled after the fruit color-turning period. The seedling whip is headed back in the year of planting, and the length was 50-60 cm. The tree should be trained cup- shaped with 3 main scaffold limbs. The main disease and pest for prevention and control are brown rot and tent caterpillar, and when pruning, you should pay attention to cut off and destroy the eggs. If there are other diseases, you need to control separately. Irrigation and white-trunk-painting should be finished before freezing days come.